SINGLE-DOSE KETOROLAC AND PETHIDINE IN ACUTE POSTOPERATIVE PAIN: SYSTEMATIC REVIEW - Ma’bud, Tasia (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: According to the International Association for the Study of Pain (IASP), pain is a sensory and emotional condition associated with tissue damage. The effectiveness of postoperative pain management facilitates patients' recovery by minimizing acute pain while facilitating their transition back to normal activities. Severe and persistent postoperative pain is reported by 2-10% of adult patients. The lack of pain evaluating methods or intervention guidelines presents a challenge for managing pain. These procedures might be helpful in improving therapy to provide a better reduction of pain. Aim: This study aims to determine whether single-dose ketorolac and pethidine effectively treat immediate postoperative pain. Methods: The study met the PRISMA 2020 guidelines by self-evaluating to ensure compliance with the rules and regulations. The investigators' aimed to make the investigation using as recent information as feasible. Publications from 2013 to 2023 were included in the identification plans using various online reference databases, including Pubmed and SagePub. Paper reviews, previously published works, and incomplete articles are excluded from consideration. Result: The PubMed record provided 43 articles, while SagePub retrieved 23 publications. In 2013, PubMed provided 14 research papers, and SagePub provided 3 papers. We collected 10 papers, 7 from PubMed and 3 from SagePub. We selected 5 research studies that fulfilled our requirements. Conclusion: According to several studies, Ketorolac injection has shown to be an effective analgesic for patients undergoing various surgical procedures.